2021
DOI: 10.2334/josnusd.20-0565
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric study of the top cited papers related to periodontal regeneration

Abstract: This report identifies the top cited papers in the field of periodontal regeneration since inception of the concept. Using the H-classics approach, 132 papers published between 1970 and 2012 were identified, with 230.0 ± 175.6 (mean ± SD) citations and 10.4 ± 11.5 citations/year. There were 46 clinical reports, 28 animal studies, 23 in vitro studies, 30 reviews, 3 systematic reviews, and 2 combined animal and in vitro studies. Analysis of covariance showed that institution number (≥3, P = 0.011), journal impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Similar studies in other fields often search the entire biomedical literature for publications in their area of interest. [2][3][4][5][6][7][8][12][13][14] However, other studies, including this one, may focus on a single journal such as the American Journal of Obstetrics and Gynecology (AJOG) or Journal of Neurosurgery. 10,11 This study was restricted to articles published in VO to mark the upcoming 25th anniversary of this journal, which is the official journal of the ACVO, and supported by virtually all of the discipline's colleges and societies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar studies in other fields often search the entire biomedical literature for publications in their area of interest. [2][3][4][5][6][7][8][12][13][14] However, other studies, including this one, may focus on a single journal such as the American Journal of Obstetrics and Gynecology (AJOG) or Journal of Neurosurgery. 10,11 This study was restricted to articles published in VO to mark the upcoming 25th anniversary of this journal, which is the official journal of the ACVO, and supported by virtually all of the discipline's colleges and societies.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the 132 top-cited articles in periodontal regeneration identified 53 (40%) basic research articles, 33 (25%) review articles, 28 (21%) clinical case reports, and (14%) clinical studies. 4 On the contrary, a study of the Top 100 articles in neurocritical care identified 57 clinical studies, 41 review articles, and two basic research articles. 3 The Top 100 articles in radiology include 52 clinical research articles, 16 articles with mixed clinical and basic research components, 14 basic research articles, and 18 "uncatergorized" articles that included 6 review articles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations